2018
DOI: 10.1159/000488824
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate Activates CCL4 Expression in Human Monocytic Cells via TLR4/MyD88 Dependent Activation of NF-κB/MAPK/ PI3K Signaling Systems

Abstract: Background/Aims: Obesity is associated with adipose tissue inflammation which plays a key role in the development of insulin resistance and type 2 diabetes (T2D). Saturated free fatty acids (SFAs) levels are found to be elevated in obesity and T2D. Chemokines are known to have potent inflammatory functions in a wide range of biological processes linked to immunological disorders. Since CCL4 (Chemokine (C-C motif) ligand 4), also known as macrophage inflammatory protein-1β (MIP-1β), plays an important role in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 30 publications
(38 reference statements)
2
45
0
Order By: Relevance
“…occur via activation of the NF-κB signaling cascade (18)(19)(20), however, mechanisms by which the complex cytokine and chemokine network in the colonic microenvironment influences inflammatory MPh infiltration are not well defined and represent a fundamental gap in the understanding of homeostatic immune function and IBD development.…”
Section: Introductionmentioning
confidence: 99%
“…occur via activation of the NF-κB signaling cascade (18)(19)(20), however, mechanisms by which the complex cytokine and chemokine network in the colonic microenvironment influences inflammatory MPh infiltration are not well defined and represent a fundamental gap in the understanding of homeostatic immune function and IBD development.…”
Section: Introductionmentioning
confidence: 99%
“…This structural requirement illustrates the exquisite specificity of the binding site in the TLR4/MD2 complex to LPS raising reservations about the potential suitability of this complex for binding alternative ligands [95]. A functional and some structural evidence exists demonstrating TLR4-dependent cell activation triggered by lipid-like molecules (e.g., lipoteichoic acid [108], minimally oxidized LDL [109], and free saturated fatty acid palmitate [110]) whose binding might be supported by a hydrophobic site on CD14. Among other proposed TLR4-activating ligands, some structural evidence exists for a chemotherapeutic drug paclitaxel (PXL) [95,101] and endogenous ligands HMGB1 [111] and S100A8 [112].…”
Section: Lps Is the Most Rigorously Confirmed Tlr4 Agonistmentioning
confidence: 97%
“…Dysregulation of lipid metabolism has been linked to tumorigenesis. It has been shown that palmitate induces CCL4 expression through TLR4-mediated pathways in monocytes [15]. Interestingly, CCL4 expression plays an important role in the migration of tumor-infiltrating lymphocytes with immunological regulatory phenotypes in melanoma [74].…”
Section: Involvement Of Palmitate In Immune-related Cell Interactionsmentioning
confidence: 99%
“…Palmitate also enhances oxidative stress-induced TLR2 and TLR4 expression in peripheral blood mononuclear cells. Moreover, in human monocytic cells, palmitate triggers matrix metalloproteinase-9 and chemokine CCL4 production via TLR4/MyD88-dependent signaling to induce subsequent metabolic inflammation [14,15], suggesting a role of innate receptors in sensing metabolic fluctuations [16]. However, whether TLRs serve as CD36 co-receptors for palmitate bioactivity remains unclear.…”
mentioning
confidence: 99%